2017
DOI: 10.1504/ijbge.2017.086480
|View full text |Cite
|
Sign up to set email alerts
|

The influence of profitability on related party revenues

Abstract: In recent decades, related party transactions (RPTs) have played a prime role in major corporate scandals, obliging regulators to strengthen the rules with new bans and costly requirements on companies. The aim of the regulatory process is to guarantee the proper use of RPTs, avoiding their incorrect use and abuse. This study contributes to the literature on RPTs, refining previous studies on this topic and providing evidence to justify the attention of lawmakers, leading to increasingly costly and mandatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Therefore, if a company is facing problems of deteriorating profitability or cash flows, it is possible that it may engage in RPTs in order to deal with that. Empirical international studies have generally found a negative relation between RPTs and financial performance (Gallery et al, 2008;Chen et al, 2009;Srinivasan, 2013;Williams & Taylor, 2013;Bava & Di Trana, 2017). Other international studies have generally found a positive relation between RPTs and leverage (Nekhili & Cherif, 2011;Utama & Utama, 2014).…”
Section: Determinants Of Related Party Transactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if a company is facing problems of deteriorating profitability or cash flows, it is possible that it may engage in RPTs in order to deal with that. Empirical international studies have generally found a negative relation between RPTs and financial performance (Gallery et al, 2008;Chen et al, 2009;Srinivasan, 2013;Williams & Taylor, 2013;Bava & Di Trana, 2017). Other international studies have generally found a positive relation between RPTs and leverage (Nekhili & Cherif, 2011;Utama & Utama, 2014).…”
Section: Determinants Of Related Party Transactionsmentioning
confidence: 99%
“…These factors include firm profitability, financial leverage, ownership concentration, CEO-duality, board size, board independence, political connections, and type of audit firm. These factors have been found by several international studies to potentially affect the application of negative RPTs that may harm some investors, especially minority investors (see, for example, Nekhili & Cherif, 2011;Munir et al, 2013;Williams & Taylor, 2013;Kang et al, 2014;Utama & Utama, 2014;Hwang & Wang, 2015;Bava & Di Trana, 2017;Boateng & Huang, 2017;Dicko, 2017;Habib et al, 2017a;Habib et al, 2017b;Bhuiyan & Roudaki, 2018;Habib & Muhammadi, 2018). While a developing country like Jordan may be vulnerable to the negative effects of RPTs, the characteristics of Jordanian companies may have their effect on the degree to which the above-mentioned factors may affect the occurrence of RPTs.…”
Section: Introductionmentioning
confidence: 99%